Putting social movements in their place : explaining opposition to energy projects in the United States, 2000-2005 - McAdam, Doug (Cambridge studies in contentious politics, 2012)
"This book reports the results of a comparative study of 20 communities earmarked for environmentally risky energy projects. The authors find the overall level of emergent opposition to the projects very low, and they seek to explain that variation and impact it had on the proposed projects"--